1996
DOI: 10.1007/bf00385801
|View full text |Cite
|
Sign up to set email alerts
|

Oral-motor skills following sensorimotor therapy in two groups of moderately dysphagic children with cerebral palsy: Aspiration vs nonaspiration

Abstract: The purpose of this study was to determine the effect of oral sensorimotor treatment on oral-motor skills and measures of growth in moderately eating impaired children with cerebral palsy who were stratified by state of aspiration/nonaspiration. Twenty-seven children aged 2.5-10.0 years participated in this study (aspiration: n = 7, nonaspiration: n = 20). Weight and skinfold measures were taken. Children were observed at lunch time and six domains of feeding were examined: spoon feeding, biting, chewing, cup … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
51
1
4

Year Published

1999
1999
2012
2012

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 35 publications
6
51
1
4
Order By: Relevance
“…Time for illness accounted for 5.5 5.17, and the time they did not wear the appliance was 22.326.47. These ®gures are well within the average we have experienced over the past 8 years[20,32]. All children (n=17) attended the three assessment sessions at M12, M18, and M24.…”
supporting
confidence: 49%
“…Time for illness accounted for 5.5 5.17, and the time they did not wear the appliance was 22.326.47. These ®gures are well within the average we have experienced over the past 8 years[20,32]. All children (n=17) attended the three assessment sessions at M12, M18, and M24.…”
supporting
confidence: 49%
“…Casaer et al [11] showed that postural controls are present in the neonate, but that they vary with behavioral state and positioning and seem to be task specific, i.e., they change with feeding. Our heightened awareness of the role of postural support/control has evolved from our studies on the efficacy of oral motor therapies in children with CP and eating impairments [12][13][14][15][16][17]. In this domain, it has become clear that the safety of ingestion is dependent on proper positioning of the head, neck, and trunk [18,19].…”
mentioning
confidence: 99%
“…Um estudo (23) verificou o efeito da intervenção sensório-motora oral em 27 crianças com PC, observando melhora nas habilidades motoras orais, com maior funcionalidade da alimentação com uso da colher, durante a mastigação e na deglutição; porém, não na ingesta de líquidos.…”
Section: Discussionunclassified